Effects of processing of feather meal on protein and energy values for pigs - Fialho, Elias Tadeu; Albino, Luiz F.T.; Thiré, Monique C.; Benetti, Ademir (Pesquisa Agropecuaria Brasileira, 2014)
Digestibility trials were conducted in order to determine the effect of pressure and cooking time of hydrolized feather meal (HFM) on dry matter digestibility coefficient (CPDC), apparent biological value of crude protein (ABVCP), digestible energy (DE), metabolizable energy (ME) and the relation between ME and DE (ME:DE), in swines. The experimental design was randomized with three repetitions. The treatments were arranged in factorial structure 2 x 6 using two pressures (1 and 3.5 kg/cm2 ) and six cooking times (30, 45, 60, 75, 90 and 105 min). It was observed that for 1 and 3.5 kg/cm2 pressure there was a quadratic relationship (P<0.01) between cooking time and DMD, CPDC and ABVCP of HFM. There was no evidence of significant effects (P>0.05) of treatments on the values of DE, ME and ME:DE of HFM. The results showed that processing only influenced the DMD, CPDC and ABVCP values of HFM. The quadratic equation showed that 3.5 kg/cm2 and 65 minutes of cooking are the better processing to obtain the hidrolized feather meal.